2020
DOI: 10.1111/are.14539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid levels on the growth, fatty acid profile and fecundity in the oriental river prawn,Macrobrachium nipponense

Abstract: An 8‐week feeding trial was conducted to investigate the effects of dietary lipid levels on growth performance, fatty acid profile and fecundity in the oriental river prawn Macrobrachium nipponense. Five isonitrogenous experimental diets were formulated with graded lipid levels [A (5.02%), B (5.98%), C (6.91%), D (7.91%) and E (8.89%) respectively]. The results indicated that the values of body weight gain, specific growth rate, protein efficiency ratio and protein retention presented a similar trend of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
5
9
0
Order By: Relevance
“…(2020) who reported that marine crabs modified dietary FAs in a similar way for each of their distinct experimental diets (suggesting a consistent strategy for lipid metabolism), we found that freshwater crayfish fed high‐quality pellets were selectively enriched in only four FAs; two long‐chain polyunsaturated FAs 20:4ω6 (ARA) and 20:5ω3 (EPA), and two monounsaturated FAs 18:1ω9 (OA) and 16:1ω7 (POA), suggesting that proportion of these molecules may be particularly important for their somatic growth. Proportion of ARA and EPA in tissues of other aquatic animals have been associated with increased growth and survival (e.g., Li et al., 2020; Nhan et al., 2020), and as discussed previously, monounsaturated FAs, such as POA and OA, are known to be important energy sources for fish (Tocher, 2003) and have been associated with ontogenetic changes to metabolism to maximise growth or for periods of fasting (Chaguaceda et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) who reported that marine crabs modified dietary FAs in a similar way for each of their distinct experimental diets (suggesting a consistent strategy for lipid metabolism), we found that freshwater crayfish fed high‐quality pellets were selectively enriched in only four FAs; two long‐chain polyunsaturated FAs 20:4ω6 (ARA) and 20:5ω3 (EPA), and two monounsaturated FAs 18:1ω9 (OA) and 16:1ω7 (POA), suggesting that proportion of these molecules may be particularly important for their somatic growth. Proportion of ARA and EPA in tissues of other aquatic animals have been associated with increased growth and survival (e.g., Li et al., 2020; Nhan et al., 2020), and as discussed previously, monounsaturated FAs, such as POA and OA, are known to be important energy sources for fish (Tocher, 2003) and have been associated with ontogenetic changes to metabolism to maximise growth or for periods of fasting (Chaguaceda et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid composition of samples was assayed by following the method of Li et al (2020). Here, the procedures were introduced briefly.…”
Section: Nutritional Composition Analysismentioning
confidence: 99%
“…Up to now, it has become one of the most important sea urchin species for aquaculture in the coastal areas of China (Zuo et al, 2018;Wang et al, 2019). At present, fresh kelp Laminaria japonica are used as the main food category for S. intermedius (Zuo et al, 2018;Li et al, 2020). However, the gonad development of S. intermedius was shown to be retarded when they were fed solely macroalgae and could be markedly accelerated after the addition of some mussel Mytilus edulis (Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐lipid content diets have been increasingly used in aquaculture because of its protein‐sparing effects (Jannathulla et al, 2019; Yigit et al, 2002), which not only reduced nitrogen waste but also decreased feed cost. Nevertheless, a high levels of dietary lipid resulted in anomalous lipid deposition and metabolic disturbance in body, which is frequently accompanied by decreased immunity in fish and shrimp (Jia et al, 2020; Li et al, 2020; Yuan et al, 2016). Hence, understanding how high‐lipid level influences the immunity and possible signalling is vital for healthy culture of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%